Cold war-era relations between west Germany and Turkish political Islam: from an anti-communist alliance to a domestic security issue - ÖZKAN, BEHLÜL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
West Germany played a significant role in the growth of Political Islam in Turkey during the Cold War. By recruiting from among Turkish workers in West Germany, Islamist organizations and the religious communities known as cemaats acquired significant economic revenues, which they used to fund their activities in Turkey. Moreover, West Germany served as a liaison between Turkish Islamists and Syrian and Egyptian Muslim Brotherhood members, who have influenced Political Islam in Turkey since the 1960s. Prominent Muslim Brotherhood representatives in West Germany took on important roles in the recruitment of Turks and also played some part in shaping the ideological development of Turkish Islamists. Due to the pervasiveness of anti-communism in West Germany and Turkey during the Cold War, the established orders in both countries viewed Political Islam as an antidote to the ascendancy of the Left. However, in the 1980s, Bonn and Ankara grew concerned about Islamist organizations becoming further radicalized and impossible to control; the two governments often cooperated in order to bring Political Islam under their own authority.
Keywords: Political Islam; Muslim brotherhood; anti-communism; Turkish politics; German politics